Review of active power filter technologies - Salam, Zainal; Tan, Perng Cheng; Jusoh, Awang (The Institution of Engineers, Malaysia, 2007)

(untitled)
Active power filters (APF), are increasingly used to mitigate harmonics in utility power lines. Compared to the more established method such as the static var compensator or passive filtering, APF are relatively new in the market. However, due to its flexibility, it is envisaged to be one of the main electrical power quality equipment of the future. Since APF is quite new in this country, awareness on its concepts, merit and benefits is not widespread. Thus the focus of this paper is to review the APF operational principles and technologies. In one sense this review can also be considered as a “tutorial-type paper” as it provides a holistic coverage of the APF technologies by omitting the tedious details, but without losing the main essence of the subject matter. It is hoped that by this approach, it would be possible to lure more power engineering readers to be involved in this important and growing field